Users taking the blame? How service failure, recovery, and robot design affect user attributions and retention - Nika Meyer (née Mozafari); Melanie Schwede; Maik Hammerschmidt; Welf Hermann Weiger (Electronic Markets, 2023)
Firms use robots to deliver an ever-expanding range of services. However, as service failures are common, service recovery actions~are necessary to prevent user churn. This research further suggests that firms need to know how to design service robots that avoid alienating users in case of service failures. Robust evidence across two experiments demonstrates that users attribute successful service outcomes internally, while robot-induced service failures are blamed on the firm (and not the robot), confirming the well-known self-serving bias. While this external attributional shift occurs regardless of the robot design (i.e., it is the same for warm vs. competent robots), the findings imply that service recovery minimizes the undesirable external shift and that this effect is particularly pronounced for warm robots. For practitioners, this implies prioritizing service robots with a warm design for maximizing user retention for either type of service outcome (i.e., success, failure, and failure with recovery). For theory, this work demonstrates that attribution represents a meaningful mechanism to explain the proposed relationships.
Keywords: M31; O32; I10; 620; Human–robot interaction; Service failure; Service recovery; Social cognition; Responsibility attribution; User retention